A Survey of Mongols and Their Successors Beliefs in Persian Context - Alavijeh, Ali Zamani (TAWARIKH, 2013)
ABSTRACT: What distinguishes the Old Mongols is their devotion to and love of Nature, the far-reaching scope of their spiritual awareness, unending mental curiosity and nearly limitless endurance, and quest for excellence in every endeavor. Since Genghis Khan is the founder of the Mongol nation, we use his name as a starting point, and see where we get if we try to compare the qualities of water with those of the Genghis-Khanite Mongols. Afterwards, we shall look more closely on their thoughts and beliefs. Hence, the Mongolian taboos, rules of restrictions, and unwritten law are traditions inherited not only from our ancestors, but also from the teachings of Genghis Khan, contained in the Code of Law of Great Mongolia called "Ikh Zasag", home to customs and traditions of the Mongolian tribes and nationalities. In the present paper, the author aims to clarify what code of conducts and principals did Mongols adhere themselves to and how they reacted in the face of new religions. We will shed light on Mongols unique respect to other religions and schools. Peerless freedom of religions prevailing in Mongol Empire will surprisingly shock those readers who had always visualized a savage and bloodthirsty picture of Mongols in their minds. The author will also survey their conversion to different religions and how these new systems affected their outlooks. Spiritual path of Mongols is the subject with which the reader will immediately acquaint himself. He/she will also shed light on the significance of symbolism in old Mongolia and their philosophical perspectives.Â  KEY WORDS: Old Mongols, Genghis Khan, code of law, devotion to and love of nature, spiritual path of Mongols, and philosophical perspectives.Â  Â About the Author: Dr. Ali Zamani Alavijeh is a Lecturer at the Department of Literature and Humanities PNU (Payame Noor University), PO Box 19395-3697, Tehran, Iran. For academic interests, the author is able to be contacted via his e-mail at: zamanialavijeh@yahoo.comHow to cite this article? Alavijeh, Ali Zamani. (2013). âA Survey of Mongols and Their Successors Beliefs in Persian Contextâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.1-16. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 12, 2013); Revised (September 15, 2013); and Published (October 28, 2013).Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Â